The theory of proportionality and its applications in comparative administrative law: a comparative analytical study - سعيد, دانا عبدالكريم; محمدأمين, بروين علي (Sulaimani Journal for Humanities, 2019)
"The theory of proportionality and its applications in the comparative administrative judiciary" The prevailing principle in jurisprudence and comparative judiciary is that judicial control stands within the limits of the discretionary authority of the administration and that it only exercises the monitoring of legitimacy. However, the administrative court, by virtue of its permanent growth and expertise, and its development of principles towards the protection of individual rights and freedoms extends its control over the work of the administration based on its discretion in order to ensure the balance and proportion between the protection of the rights and freedoms of individuals on the one hand, and to enable the administration to achieve its increasingly complex objectives as a result of developments in all areas of life. This research focuses on the theory of proportionality as one of the most important modern theories created by the comparative administrative judiciary, and on the other hand its applications, especially in the field of administrative monitoring, in the field of disciplinary sanctions for government officials.